Second Order Impulsive Retarded Differential Inclusions with Nonlocal Conditions - Henriquez-Miranda, H (2014)
In this work we establish some existence results for abstract second order Cauchy problems modeled by a retarded differential inclusion involving nonlocal and impulsive conditions. Our results are obtained by using fixed point theory for the measure of noncompactness. © 2014 Hernán R. Henríquez et al.